The Effect Of Socio-Technical Enablers On Knowledge Sharing Behaviour Among Academician In Iran With Social Network Ties As A Moderator - Jahani, Shiva (2012)
Nowadays, knowledge management (KM) is recognised as an important capability that opens the key to competitive advantage for many practitioners and academicians. Researchers have argued the most important part of KM is that individuals are the main mover of knowledge creation in an organization. Knowledge sharing behaviour is an essential part of KM. Nowadays, recognised by business as a potential source of competitive advantage. The development of any society, in economic, cultural, social, and political dimensions, influences its human resources. Education is recognised as a major factor in human resource development. Universities are the supreme creator of knowledge, innovation and proficiency, taking on the vital role developing human capital as the base of societal growth and development. In this role, it is important that university research responds to the changing modern day environment. This thesis addresses the issues of knowledge sharing behaviour as a promising area of study and has the capability to provide vital benefits to higher education institutions. The study tries to identify key enablers (organizational environment, individual factors and information technology usage) to knowledge sharing behaviour and the outcomes (intellectual output) of these practices. In addition, the study examines the effects of social network ties as a moderator between knowledge sharing behaviour and intellectual output. Data collected through the mailed survey.